Cytogenotoxic, insecticidal, and phytotoxic activity from biomass extracts of the freshwater algae Nitella furcata. Issue 4 (16th February 2023) - da Silva, Regildo Márcio Gonçalves; de Andrade, Aníbal Reinaldo; Granero, Filipe Oliveira; Figueiredo, Célia Cristina Malaguti; dos Santos, Valter Henrique Marinho; Machado, Levi Pompermayer; Pereira Silva, Luciana
ABSTRACT: Agroecology, the application of ecological concepts to agricultural production, has been developing over the last years with consequent promotion for discovery of bioactive compounds to control pests and abolish crop diseases. In this context, algae from Nitella genus are characterized by high potential for bioeconomic applications due to (1) available biomass for harvesting or cultivation and (2) production of allelochemicals, which present a potential to protect field crops from insect infestation. Therefore, this study aimed to determine primary and secondary metabolites derived from aqueous and hydroethanolic extracts of Nitella furcata and to evaluate phytotoxic, cytogenotoxic, insecticidal, and pro-oxidative activities of these extracts. Determination of metabolites showed the presence predominantly of carbohydrates, proteins, phenols, and flavonoids in hydroethanolic extract. Both extracts of N. furcata interfered in the germination of seeds and development of seedlings of Lactuca sativa, with hydroethanolic extract exhibiting greater inhibition. Both extracts also interfered with meristematic cells of Allium cepa as evidenced by chromosomal alterations and higher pro-oxidative activity. Aqueous extract at 5 and 0 mg/ml produced 100% insect mortality. Further, hydroethanolic extract at 0 mg/ml was lethal immediately upon exposure. Therefore, results demonstrate that N. furcata is potential algae species to be considered for development of environmental and ecotoxicological studies as a source of compounds with potential use in agroecological strategies.